System degradation due to phase error induced crosstalk in WDM optical networks employing arrayed waveguide grating multi/demultiplexer - Sim, E. C.; Abbou, F. M.; Faidz, A. R. (Springer, 2007)
The phase error induced crosstalk within arrayed waveguide gratings (AWG) have been investigated theoretically as well as simulation. For WDM system, a crosstalk level of -21.9 dB causes a power penalty of 1 dB for 64 channels and less than 0.5 dB for 16 channels and 32 channels, respectively. For crosstalk level of -30 dB and below, the power penalty is negligible. Crosstalk due to phase error also causes higher power penalty at higher bit rate. Bit rate of 10, 20 and 40 Gbits/s causes power penalty of 1 dB with crosstalk level of -41.5, -46.25 and -49 dB, respectively.